Effect of Sleeve Gastrectomy on Thyroid Function in Chinese Euthyroid Obese Patients. Issue 4 (August 2017) - Yang, Jingge; Gao, Zhiguang; Yang, Wah; Zhou, Xiangmao; Lee, Shing; Wang, Cunchuan
Abstract : Background: Changes in thyroid function following bariatric surgery in euthyroid obese patients have yielded inconsistent results. Nevertheless, no data exist on changes in thyroid function after bariatric surgery in Chinese obese subjects. Objectives: The objective of this study is to evaluate the influence of weight reduction on thyroid function following laparoscopic sleeve gastrectomy (LSG) in patients with normal thyroid function. Patients and Methods: Serum free thyroxine (FT4), free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH) levels were retrospectively analyzed before and 12 months after LSG in euthyroid patients with morbid obesity. Correlation between weight loss after LSG and changes in thyroid function were investigated. Results: In total, 16 patients who underwent LSG were included in the study. Mean BMI change from 35.78 to 23.66 kg/m 2 ( P <0.000) after LSG was associated with a mean reduction in the TSH from 2.31 to 1.54 mU/L ( P =0.022), whereas FT4 (15.19±0.33 pmol/L at baseline and 14.85±0.58 pmol/L at 12 mo after LSG; P =0.583) and FT3 (4.98±0.15 pmol/L at baseline and 4.77±0.60 pmol/L at 12 mo after surgery; P =0.406) levels remained steady. Decrease in TSH was significantly correlated with decrease in BMI at 12 months after surgery but did not correlate with excess weight loss and total weight loss. Conclusions: Weight loss after LSG is accompanied by significant decrease in serum TSH level but no change in serum FT4 and FT3 levels. However, further work is required to elucidate the mechanism.